1969
DOI: 10.1002/1097-0142(196904)23:4<920::aid-cncr2820230430>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Midline malignant reticulosis (so-called lethal midline granuloma)

Abstract: “Lethal midline granuloma” should be only a clinical term for rapidly evolving destructive lesions of the nose and the deep facial tissues. Such clinical presentation—after specific infections and carcinomas have been excluded—may occur in 3 different clinicopathologic entities: midline malignant reticulosis (polymorphic reticulosis), Wegener's granulomatosis, and malignant lymphoma of one of the accepted histologic types. One representative case of each of these is reported here, histologic criteria for diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(16 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…My own studies of the available evidence and experience of a group of s-ich patients substantiates the view of Kassal et al 16 Provided diagnosis is early the prognosis of patients with such a "neoplastic change" remains better than when a malignant lymphoma occurs de novo in the nose. All nine patients reported by EicheP17 in 1966 survived at least five years after curative radiotherapy, and my own three patients all showed a favourable response.…”
Section: Case 12supporting
confidence: 57%
See 1 more Smart Citation
“…My own studies of the available evidence and experience of a group of s-ich patients substantiates the view of Kassal et al 16 Provided diagnosis is early the prognosis of patients with such a "neoplastic change" remains better than when a malignant lymphoma occurs de novo in the nose. All nine patients reported by EicheP17 in 1966 survived at least five years after curative radiotherapy, and my own three patients all showed a favourable response.…”
Section: Case 12supporting
confidence: 57%
“…Kassal et al 16 suggested that non-healing granuloma should be regarded as a form of maliznant midline reticulo'is. the disease usually remaining localized but eventually overcoming immunological control with possible visceral dissemination.…”
Section: Case 12mentioning
confidence: 99%
“…ENKTL was previously known as lethal midline granuloma because, macroscopically, the tumor looked like a necrotic granuloma, and the disease showed an aggressive and lethal course [30], [31]. Histologically, ENKTL is characterized by angiocentric and polymorphous lymphoreticular infiltrates, known as polymorphic reticulosis [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent report in 1921 [88] described two patients with destructive nasal lesions, in whom syphilis was excluded as a diagnosis and no infectious organism could be identified. Further clinical and histological accounts of such a disease accumulated over the following decades [89-95]. Various terminologies for ENKTL have been used, including: lethal midline granuloma, rhinitis gangrenosa progressiva, polymorphic reticulosis, and malignant midline reticulosis.…”
Section: Extra-nodal Nk/t-cell Lymphoma Nasal Typementioning
confidence: 99%